2003
DOI: 10.4049/jimmunol.170.3.1504
|View full text |Cite
|
Sign up to set email alerts
|

Bordetella pertussisInfection in 2-Month-Old Infants Promotes Type 1 T Cell Responses

Abstract: Neonatal immaturity of the immune system is currently believed to generally limit the induction of immune responses to vaccine Ags and to skew them toward type 2 responses. We demonstrated here that Bordetella pertussis infection in very young infants (median, 2 mo old) as well as the first administration of whole-cell pertussis vaccine induces B. pertussis Ag-specific IFN-γ secretion by the PBMC of these infants. IFN-γ was secreted by both CD4+ and CD8+ T lymphocytes, and the levels of Ag-induced IFN-γ secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 39 publications
3
90
0
3
Order By: Relevance
“…Several earlier studies indicated that B. pertussis infection promotes a Th1 immune response, based largely on IFN-␥ production (37)(38)(39). We have previously demonstrated that incubation of human MDDC with B. pertussis induced a Th1 predominant polarization and expression of IL-23, involved in Th17 cell expansion, in the absence of the Th1-inducing cytokine IL-12p70 (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Several earlier studies indicated that B. pertussis infection promotes a Th1 immune response, based largely on IFN-␥ production (37)(38)(39). We have previously demonstrated that incubation of human MDDC with B. pertussis induced a Th1 predominant polarization and expression of IL-23, involved in Th17 cell expansion, in the absence of the Th1-inducing cytokine IL-12p70 (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…This 105-kDa protein complex is produced by Bordetella pertussis, the bacterium responsible for whooping cough in humans. PTx is immunogenic and involved in the pathogenesis of B. pertussis infection (7,8) and, therefore, has been included in some acellular pertussis vaccines in a chemically or genetically detoxified form (9).…”
Section: P Ertussis Toxin (Ptx)mentioning
confidence: 99%
“…These responses have been associated with a variety of functional cytokines [11,13,60,61]. Recovery from whooping cough in older infants is associated with induction of T lymphocytes producing Th1-type cytokines IFN-γ and IL-2 [61]. Studies in very young children (2 months of age) show that natural infection with B. pertussis or a first administration of WCV can promote maturation of Th1-type responses [61,62].…”
Section: Induction and Maintenance Of Pertussis Immunitymentioning
confidence: 99%
“…Recovery from whooping cough in older infants is associated with induction of T lymphocytes producing Th1-type cytokines IFN-γ and IL-2 [61]. Studies in very young children (2 months of age) show that natural infection with B. pertussis or a first administration of WCV can promote maturation of Th1-type responses [61,62]. By contrast, the widely used ACV vaccines also induce Th2-type cytokine (IL-4 and IL-5) responses to concomitant vaccine antigens in infants [60,62], becoming more pronounced when given closer to birth [63,64].…”
Section: Induction and Maintenance Of Pertussis Immunitymentioning
confidence: 99%
See 1 more Smart Citation